The ground states of hidden-charm tetraquarks and their radial excitations - Guo-Liang Yu; Zhen-Yu Li; Zhi-Gang Wang; Bin Wu; Ze Zhou; Jie Lu (European Physical Journal C: Particles and Fields)
Abstract Inspired by the great progress in the observations of charmonium-like states in recent years, we perform a systematic analysis about the ground states and the first radially excited states of $$qc\bar{q}\bar{c}$$ q c q ¯ c ¯ (q = u/d and s) tetraquark systems. Their mass spectra, root mean square (r.m.s.) radii and radial density distributions are predicted within the framework of relativized quark model. By comparing with experimental data, some potential candidates for hidden-charm tetraquark states are suggested. For $$qc\bar{q}\bar{c}$$ q c q ¯ c ¯ (q = u/d) system, if $$Z_{c}(3900)$$ Z c ( 3900 ) is supposed to be a compact tetraquark state with $$J^{PC}=1^{+-}$$ J PC = 1 + - , Z(4430) can be interpreted as the first radially excited states of $$Z_{c}(3900)$$ Z c ( 3900 ) . Another broad structure $$Z_{c}(4200)$$ Z c ( 4200 ) can also be explained as a partner of $$Z_{c}(3900)$$ Z c ( 3900 ) , and it arise from a higher state with $$J^{PC}=1^{+-}$$ J PC = 1 + - . In addition, theoretical predictions indicate that the possible assignments for X(3930), X(4050) and X(4250) are low lying $$0^{++}$$ 0 + + tetraquark states. As for the $$sc\bar{s}\bar{c}$$ s c s ¯ c ¯ system, X(4140) and X(4274) structures can be interpreted as this type of tetraquark states with $$J^{PC}=1^{++}$$ J PC = 1 + + , and X(4350) can be described as a $$sc\bar{s}\bar{c}$$ s c s ¯ c ¯ tetraquark with $$J^{PC}=0^{++}$$ J PC = 0 + + . With regard to $$qc\bar{s}\bar{c}$$ q c s ¯ c ¯ (q = u/d) system, we find two potential candidates for this type of tetraquark, which are $$Z_{cs}(4000)$$ Z cs ( 4000 ) and $$Z_{cs}(4220)$$ Z cs ( 4220 ) structures. The measured masses of these two structures are in agreement with theoretical predictions for the $$1^{+}$$ 1 + state.